Identifikasi Pola Permukiman Tradisional Kampung Budaya Betawi Setu Babakan, Kelurahan Srengseng Sawah, Kecamatan Jagakarsa, Kota Administrasi Jakarta Selatan, Provinsi DKI Jakarta - MOECHTAR, MUHAMMAD SYAIFUL; SARWADANA, SANG MADE; SEMARAJAYA, COKORDA GEDE ALIT (Jurnal Agroekoteknologi Tropika (Journal of Tropical Agroecotechnology); Vol. 1, No. 2, Oktober 2012, 2012)
ABSTRACT The Identification of Traditional Settlement Patterns of Setu Babakan Betawinese Cultural Village, District of Srengseng Sawah, Subdistrict of Jagakarsa, South Jakarta, the Province of  DKI JAKARTA The objective of the research is to show an evidence that the form of traditional settlement patterns of Betawinese does still exist in DKI Jakarta. The method used is descriptive quantitative, in which data source was derived from the literature study, observations, structured interviews, and questionnaires (30 respondents). The results of the research showed that Setu Babakan Betawinese Cultural Village settlement patterns uses clustered settlement pattern which follows the circular shape of the Lake/Setu Babakan, and has the characteristic of clustered spread distribution pattern. The former elements in this settlement are physical, economical and social cultural, and they are inter-related. This settlement has the area about 289 ha (67 ha owned by the Local Government) with the percentage of built-up space by 61.17% and 38.83% undeveloped area (include water bodies). The spatial patterns in Setu Babakan was not visible any philosophical history or any clear layout. The existing vegetations in the settlement are of particularly those plants with the characteristic of Betawi producing plants, such as Durio zibetinus Var. Sitokong, Baccaurea racemosa and Sandoricum loetjape . The results of research in the field, 43% of existing plants in the settlements has functioned as a producing plants. This Betawinese settlement is a typical “suburban Betawinese settlement”, which has two types of traditional houses, Rumah Gudang and Bapang /Kebaya and do not have the wind direction and specific orientation in placement. Keyword : traditional settlement patterns, Betawinese, clustered settlement
Keywords: traditional settlement patterns, Betawinese, clustered settlement